An analysis of relationship between Malaysia economic growth and inflation in the previous economic policy / Tismazammi Mustafa, Hapiza Omar and Iskandar Hasan Tan Abdullah - Mustafa, Tismazammi; Omar, Hapiza; Abdullah, Iskandar Hasan Tan (2012)
The most important basic objectives for any countries in this world are to sustain high economic growth with low inflation. Thus, this study attempts to investigate the relationship between economic growth rate and inflation rate in Malaysia based on Previous Policy of Malaysia. Using the annual data for the period 1970-2008, economic root test unit, integration test and Granger Causality test are used. According to this study, the empirical results showed that the data is stationary at level. The finding also shown the results integrate in long run relationship between inflation rate and economic growth rate. The Granger Causality test did not show bidirectional between economic growth rate and inflation rate. But, a uni-directional causality is found from inflation rate to economic growth rate. Hence, there is exist short run causality between variables in uni-directionally.